Methanol-induced fast CsBr release results in phase-pure CsPbBr3 perovskite nanoplatelets. Issue 5 (30th March 2020) - Liu, Xin; Luo, Zhao; Yin, Wenxu; Litvin, Aleksandr P.; Baranov, Alexander V.; Zhang, Jiaqi; Liu, Wenyan; Zhang, Xiaoyu; Zheng, Weitao
Abstract : A suitable minor amount of a methanol additive leads to bright, monodispersed and phase-pure 8 unit-cell-thick CsPbBr3 NPLs. Abstract : Formation of a non-emissive wide bandgap CsPb2 Br5 component often accompanies the synthesis of CsPbBr3 perovskites, introducing undesired energy states and impeding the charge transport. Here, we demonstrate that a small amount of a methanol additive can promote the CsBr release rate, facilitating CsPbBr3 formation and suppressing CsPb2 Br5 formation. Some of the methanol ionizes into CH5 O + and CH3 O −, which act as surface ligands and change the crystallization environment, inducing shape evolution from spherical nanocrystals to rectangular nanoplatelets (NPLs), leading to monodispersed and phase-pure 8 unit-cell-thick CsPbBr3 NPLs. Meanwhile, nonradiative recombination processes are inhibited as a result of NPL surface passivation. Bright CsPbBr3 NPLs with a photoluminescence quantum yield reaching 90% were employed as emitters for electroluminescent light-emitting devices.